Applying an Appropriate Standard of Evidence in Victim Identification Policies and Practice in Cambodia, Indonesia, Malaysia, Myanmar, Philippines, and Thailand - Cauton , Gideon Elfred (Journal of Interdisciplinary Perspectives, 2023)
Human trafficking remains to be a bane in our time undermining economic progress and perpetuating inequities by setting vulnerable communities who fall prey to it further back. This vicious cycle increases the risk of re-trafficking for victims who escape, and leaves layered trauma experiences unaddressed. To counter this, labor-receiving countries need to connect human trafficking victims to social services that utilize victim-centered and trauma-informed approaches geared toward victim restoration. Often the first step in accessing these services is victim identification. However, officers of government frontline agencies with the mandate to enforce the anti-human trafficking law apply very strict standards in their screening method. The perceived outcome of cases in trial plays a crucial role in victim determination. Thus, there is the tendency to apply evidentiary standards appropriate for a court trial in victim identification. Such practice tends to be adversarial where the burden of proof is paced on the victim’s shoulders. Utilizing the standards of evidence as a conceptual framework has the potential of shifting rigid procedures and processes. The standards of evidence framework can calibrate and adjust current practices in victim identification to the appropriate threshold in favor of potential victims of trafficking accessing and receiving victim-centered services.